Perceived Stress at Work Is Associated with Lower Levels of DHEA-S - Lennartsson, Anna-Karin (Public Library of Science, 2013)
BACKGROUND: It is known that long-term psychosocial stress may cause or contribute to different diseases and symptoms and accelerate aging. One of the consequences of prolonged psychosocial stress may be a negative effect on the levels of dehydroepiandrosterone (DHEA) and its sulphated metabolite dehydroepiandrosterone sulphate (DHEA-S). The aim of this study is to investigate whether levels of DHEA and DHEA-S differ in individuals who report perceived stress at work compared to individuals who report no perceived stress at work. METHODS: Morning fasting DHEA-S and DHEA levels were measured in serum in a non-stressed group (n = 40) and a stressed group (n = 41). DHEA and DHEA-S levels were compared between the groups using ANCOVA, controlling for age. RESULTS: The mean DHEA-S levels were 23% lower in the subjects who reported stress at work compared to the non-stressed group. Statistical analysis (ANCOVA) showed a significant difference in DHEA-S levels between the groups (p = 0.010). There was no difference in DHEA level between the groups. CONCLUSIONS: This study indicates that stressed individual have markedly lower levels of DHEA-S. Given the important and beneficial functions of DHEA and DHEA-S, lower levels of DHEA-S may constitute one link between psychosocial stress, ill health and accelerated ageing.